The Phenomenon of Intertextuality in Ibn Muzaffar al-Hatimi through his book *Hilyat al-Muhadara - Cheikh, Abdelrazak; marrok, aissa (El Omda in Linguistics and Discourse Analysis, 2023)
Arab critics have known and studied multiple forms of Intertextuality in their blogs. If they do not take the modern term, they have studied it in the name of literary thefts, It was not good, it was ba, including of whom Al-Muzaffar Al-Hitami, Who will try to track the term intertextuality in author "Hilyat almehadara" which many scholars relied on, It may achieve a part of rooting For the theory of Intertextuality within a specific context in the Field of Knowledge and Critical Practice. See the intersections of this text with Monetary Statements that I contemplated followed by Especially in our present era.